(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
To study the morphological changes of peritumarous zones in kidney cancer, immunohistochemical examination methods were performed. 63 patients operated on for kidney cancer in 2017-2022 were selected for immunohistochemical examination. In 20 of them, repeated immunohistochemical examinations of the peritumarose zone were performed with the study of the obtained micro-preparations. Immunohistochemical testing was performed using Ki67, P53, CD34, CD3, and CD20 antigens.